Early to middle Jurassic stratigraphic development, vegetation and climate change in north-western Europe - Morgans, H; Morgans, Helen Sarah (1997)
﻿ The aim of work presented in this thesis was to explore the inter-relationships of cyclic sedimentation, relative sea-level change, and palaeoclimate as inferred from plant megafossils. To this end, the investigation focused on the classic plant-bearing Middle Jurassic succession of Yorkshire. The Middle Jurassic (Aalenian-Bathonian) Ravenscar Group of the Cleveland Basin (Yorkshire) comprises a predominantly fluvio-deltaic succession intercalated between thinner, laterally persistent marine units. There is a pronounced lateral facies change across the basin, from mainly alluvial sediments in the north to more marine deposits in the south. Although variable in character, the facies composing the sequence are described by four principal environments of deposition: alluvial, estuarine, lagoonal and marine. In an attempt to achieve a more accurate stratigraphic control on the succession, sequence-stratigraphic concepts are applied to outcrop exposures and subsurface cores. The identification of 'key surfaces' in the sequence resolves a series of lithological cycles which reflect relative sea-level fluctuations. Using this approach the Aalenian-Bathonian sequence can be subdivided into two large-scale (second-order) transgressive-regressive cycles onto which six medium-scale (thirdorder) cycles of transgression and regression are superimposed. The potential for correlating these lithological cycles regionally has been assessed by comparing coeval sections from southern Scandinavia. Plant-bearing fluvio-deltaic sequences from Bornholm and Scania were chosen as a means for appraising the lateral continuity of the cycles, and assessing what factors might have controlled their development. Study of floral remains from the Ravenscar Group within the context of this stratigraphic framework yields valuable palaeoclimatic information. Growth-ring analysis of fossil wood of Late Pliensbachian to Late Bathonian age indicates a distinctly seasonal climate with low to moderate interseasonal variation in tree growth. Significant intraseasonal influences on wood production are implicit in the abundance of false rings. Consideration of these results within a stratigraphic context suggests that conditions during the Bathonian were comparatively hostile: a finding which is interpreted to be due to more frequent and extended water shortages associated with a drier climate. These palaeoclimatic inferences are substantiated by evidence obtained from the examination of the flora using Correspondence Analysis (CA). This approach verifies the presence of a temporal fluctuation in the flora found by previous investigations and, furthermore, highlights physiognomic trends in the flora with time. The results from CA also indicate adverse growing conditions during the Bathonian, emphasized by the prevalence of xeromorphic taxa.